Новые ископаемые прямокрылые семейств Adumbratomorphidae fam. n., Pruvostitidae и Proparagryllacrididae (Orthoptera, Ensifera) из пермских и триасовых отложений СССР - Горохов, А.В. (Вестник зоологии, 1987)
New finds of the fossil Orthoptera Ensifera are described from the Perm of Urals and Trias of Kirghizia. A new family is established. The system of Proparagryllacrididae is revised with description within it of three new subfamilies. Nine new genera and 15 new species are described.